Perubahan kadar albumin dan prealbumin etelah suplementasi ekstrak ikan gabus metode freeze dryer pada pasien sepsis - Ahmad Fiza Putera; Achsanuddin Hanafie; Dadik Wahyu Wijaya (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction : Septic is the second highest cause of death in Intensive Care Unit and 10 highest cause of death in the world overall. Mortality and Morbidity of sepsis in relation with hypoalbuminemia, with the number incidence 60-70%. The principal of nutritional management in septic patient is how to manage calories and high protein to balance the catabolic process. Extract of snakehead fish is the source of high protein in compare with other sources. The purpose of this study is to know the level of albumin and prealbumin after the sumplementation of extract of snakehead fish with the freezy dryer methode. Methodes : The Randomized Control Trial double blinded which done in Mei-June 2016 in Rumah Sakit Umum Pusat Haji Adam Malik Medan. The total of 38 Patients whose included in inclusive and exclusive criteria for this research. Level of albumin and preabulmin was measuring after the suplementation extract of snakehead fish with the methode of freezy dryer as suplementation of protein as a enteral nutrition in 3 days intervention. In a group with suplementation extract of snake head fish with the methode of freezy dryer increased the level of albumin 0.26 gr/dL (p<0.001) and the level of prealbumin 9.36 mg/dL (p<0.001). In difference with the group given placebo, the level of albumin decreased 0.32 gr/dL (p<0.001) and the decreased of prealbumin 4.58 mg/dL (p<0.001).Result : Extract of snakehead fish with the freezy dryer extraction could increase 0.26 mg/dL albumin level and 11.26 mg/dL prealbumin level.Conclussion : suplementation of snakehead fish with the freezy dryer methode could increase albumin and prealbumin level efectively.Keyword : additional protein intake, hypoalbuminemia, nutrition, sepsis